Stress distribution on dentin-cement-post interface varying root canal and glass fiber post diameters. A three-dimensional finite element analysis based on micro-CT data - Priscilla Cardoso LAZARI; Rodrigo Caldeira Nunes de OLIVEIRA; Rodolfo Bruniera ANCHIETA; Erika Oliveira de ALMEIDA; Amilcar Chagas FREITAS JUNIOR; Sidney KINA; Eduardo Passos ROCHA (University of São Paulo, 2013)
Objective: The aim of the present study was to analyze the influence of root canal and glass fiber post diameters on the biomechanical behavior of the dentin/cement/post interface of a root-filled tooth using 3D finite element analysis. Material and Methods: Six models were built using micro-CT imaging data and SolidWorks 2007 software, varying the root canal (C) and the glass fiber post (P) diameters: C1P1-C=1 mm and P=1 mm; C2P1-C=2 mm and P=1 mm; C2P2-C=2 mm and P=2 mm; C3P1-C=3 mm and P=1 mm; C3P2-C=3 mm and P=2 mm; and C3P3-C=3 mm and P=3 mm. The numerical analysis was conducted with ANSYS Workbench 10.0. An oblique force (180 N at 45º) was applied to the palatal surface of the central incisor. The periodontal ligament surface was constrained on the three axes (x=y=z=0). Maximum principal stress (σmax) values were evaluated for the root dentin, cement layer, and glass fiber post. Results: The most evident stress was observed in the glass fiber post at C3P1 (323 MPa), and the maximum stress in the cement layer occurred at C1P1 (43.2 MPa). The stress on the root dentin was almost constant in all models with a peak in tension at C2P1 (64.5 MPa). CONCLUSION: The greatest discrepancy between root canal and post diameters is favorable for stress concentration at the post surface. The dentin remaining after the various root canal preparations did not increase the stress levels on the root.